Catalytic and stoichiometric oxidation of N, N-dimethylanilines mediated by nonheme oxoiron(IV) complex with tetrapyridyl ligand. (1st September 2019) - Lakk-Bogáth, Dóra; Kripli, Balázs; Meena, Bashdar I.; Speier, Gábor; Kaizer, József
Graphical abstract: Catalytic activity and selectivity of [Fe II (N4Py * )(CH3 CN] 2+, where the possible reactive high-valent intermediate (Fe IV O) is known and spectroscopically well characterized, was studied in the oxidation of DMA derivatives, utilizing PhIO, TBHP, H2 O2, PAA and mCPBA as co-oxidants. Abstract: Nonheme iron(II) complex, [(N4Py * )Fe II (CH3 CN)](ClO4 )2 (1 ) with pentadentate tetrapyridyl ligand (N4Py *  =  N, N -bis(2-pyridylmethyl)-1, 2-di(2-pyridyl)ethylamine) has been shown to catalyze the oxidation of N, N -dimethylaniline (DMA) with H2 O2, tert -butyl hydroperoxide (TBHP), peracetic acid (PAA), meta -chloroperoxybenzoic acid (mCPBA) and PhIO resulting N -methylaniline (MA) as the predominant product with N -methylformanilide (MFA) as a result of a free-radical chain process. The product composition (MA/MFA) is remarkably influenced by the electron density on the substrate, especially in the1 /mCPBA system, and by the co-oxidants used. No formation of MFA occurred when the oxidation of DMA was carried out in the presence of1 with PhIO as co-oxidants under argon. Based on spectral investigation (UV–Vis) of reaction systems above, oxoiron(IV) intermediate, [Fe IV (N4Py * )(O)] 2+ (2 ) has been suggested to be the key active species of the N -dealkylation reaction in all catalytic systems. The shift in the λ max value of the oxoiron(IV) species in the presence of DMA from 705 to 750 nm, and the new intense absorption in the range of 5–600 nm indicates a complexation and charge-transfer (CT) type interactions between the oxidant and substrate. The stoichiometric oxidation of various N, N -dimethylaniline derivatives with2 provided clear evidence (Hammett correlation with ρ  = −1.99, and the large negative slope (−4.1) from the log k obs versus E o ox (DMAs) plot) for the rate-determining electron transfer (ET) followed by a proton transfer (PT) process.